Central granular cell odontogenic tumour associated with sepsis, osteonecrosis and osteomyelitis. (29th December 2021) - Comitale, Ernesto; Roccon, Andrea; Fedrigo, Marny; Angelini, Annalisa; Zanette, Gastone; Bacci, Christian
Abstract: Central granular cell odontogenic tumour (CGCOT) is a rare odontogenic benign neoplasm with only 39 cases reported in the literature. This report describes an unusual case of CGCOT as it was associated with severe signs of local and systemic infection. The patient was hospitalised for sepsis, high fever and facial swelling. The intraoral examination and the radiographic images led to the clinical diagnosis of periapical abscess caused by a severely decayed left maxillary third molar. After the surgical extraction of the tooth, a periapical lesion and fragments of the alveolar process were sent for histopathologic examination and immune‐phenotypic characterisation. The pathological findings became crucial for the definitive diagnosis of CGCOT, osteonecrosis and osteomyelitis. The purpose of this report is to provide knowledge about this tumour and highlight the importance of sending samples collected during oral surgery for histopathologic examination.